Eksistensi Etnis Cina di Bawah Pemerintahan Orde Baru, 1966-1998 - Sibawati, Ihzanda (Yayasan Alpatih Harapan Semesta, 2024)
This research aims to examine the existence of ethnic Chinese in Indonesia under the New Order government, namely in 1966-1998, a period marked by policies of assimilation and strict control over ethnic minority groups. The New Order government, led by Suharto, implemented various regulations that limited cultural freedom and Chinese ethnic identity, such as prohibiting the use of Mandarin in public spaces, limiting cultural tra ditions, and changing names to Indonesians. Systematic discrimination and anti-Chinese sentiment are exacerbated by ambiguous economic policies, where although ethnic Chinese play an important role in the economic sector, they still face negative stereotypes and accusations of economic monopoly. This research uses a qualitative approach with literature study methods and document analysis to explore the impact of New Order policies on the socio-economic life and cultural identity of ethnic Chinese. The fin dings in this study in dicate that despite discrimination, ethnic Chinese developed various adaptation strategies, inclu ding identity adjustment and stronger economic integration, to survive in a repressive environment. This study also reveals that although the assimilation policy aimed to erase ethnic differences, ethnic Chinese were still able to maintain certain aspects of their cultural identity, both openly and privately. This research emphasizes the need to reflect on the history of discrimination against ethnic Chinese and the importance of buil ding inclusive policies that respect diversity as part of reconciliation efforts in post-New Order Indonesia.